World and us - Unger, Roberto Mangabeira (London ; New York : Verso, 2024)
"Roberto Mangabeira Unger sets out to reinvent philosophy. His central theme is our transcendence-everything in our existence points beyond itself-and its relation to our finitude: everything that surrounds us, and we ourselves, are flawed and ephemeral. He asks how we can live so that we die only once, instead of dying many small deaths; how we can breathe new life and new meaning into the revolutionary movement that has aroused humanity for the last three centuries, but that is now weakened and disoriented; and how we can make sense of ourselves without claiming for human beings a miraculous exception to the general regime of nature. For Unger, philosophy must be the mind on fire, insisting on our prerogative to speak to what matters most"--
Includes index.
Keywords: Transcendence (Philosophy)